Direct Investigation of Synthesis of Gold Nanoparticles Using Polyscias scutellaria Leaf Extract in the Hexane-Water System Using the Centrifugal Liquid Membrane-Spectrophotometry Method - Muhammad Rizki Kurniawan; Aji Humaedi; Ahmad Fitra Ritonga (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
The Centrifugal liquid Membrane (CLM) method, which provides an ultra-thin two-phase liquid membrane system in a rotating glass cell, was successfully applied to Green Synthesis from Polyscias scutellaria (PS) capped gold nanoparticles (AuNPs-PS) using a Mangkokan leaf (Polyscias scutellaria) extract as a reducing agent and stabilizer in the hexane-water system. PS extract in hexane fraction as the organic phase has a UV absorption spectrum at the maximum wavelength, λmax of 220 nm, while the precursor of HAuCl4 solution as an aqueous phase has an λmax of 214 nm. Investigation of AuNPs-PS formation was carried out at various concentrations of Mangkokan leaf extract concentration; i.e., 0.001 0.003; 0.005; 0.007 and 0.009%, while the reaction was carried out at various rotational speeds of 5,000-9,000 rpm. The formation and stability of AuNPs-PS were observed from the phenomenon of surface plasmon resonance (SPR) and absorbance changes as measured by a UV-Vis spectrophotometer. The results of measurements using CLM-Spectrophotometry shows the formation of AuNPs-PS in the hexane-water system at λmax of 534 nm.